Analysis on fat-soluble components of sinapis semina from different habitats by GCâMS - Cheng Peng; Tao Zhang; Gang Zhao; Sicen Wang (Elsevier, 2013)
A simple and rapid gas chromatography/mass spectrometry (GC/MS) analysis method was developed for the determination of fat-soluble parts of sinapis semina. Four major compounds were chosen as marker compounds to evaluate the method. Various extraction techniques were evaluated and the greatest efficiency was observed with sonication extraction using diethyl ether. The method was valuated as follows: acceptable apparatus suitability was obtained by testing the resolutions, tailing factors and theoretical plate number of the marker compounds; the precision and reproducibility, expressed as relative standard deviation (RSD), fell within the prescribed limits. Eight samples of sinapis semina collected from markets in Xi'an were monitored by using the method. The fingerprints of those samples were analyzed by hierarchical cluster analysis (HCA) similarity analysis. The result indicated that the combination of fingerprint and HCA could be used to analyze sinapis semina from different habitats. Keywords: Sinapis semina, Sonication extraction, GC/MS, Fingerprint, HCA